Smart Cylindrical Dome Antenna Based on Active Frequency Selective Surface - Tongyu Ding; Shaoqing Zhang; Liang Zhang; Yanhui Liu (International Journal of Antennas and Propagation)
In this paper, we proposed a beamforming antenna, which is realized using an omnidirectional antenna in the center surrounded by a cylindrical smart dome. The smart dome is made of 16 active frequency selective surface columns of which the amplitude and phase response can be continuously tuned by varying the bias voltages of the employed varactors. Thus, the performance of the proposed antenna could achieve higher gain, better nulling level, and more agility than many switch methods-based cylindrical reconfigurable antennas. Moreover, in order to overcome the unavailable analytical synthesis caused by complex mutual coupling between columns, we develop a genetic algorithm based optimization system and conducted a serial of experiments to evaluate the high-gain, nulling, continuously steering, and frequency-invariant ability. The results show that, during the frequency tunable range of the AFSS (2.0 GHz to 2.7 GHz), the antenna can offer an additional gain of up to 6.57 dB and nulling level of −56.41 dBi. For the high-gain modes, the −3 dB beam widths are 26°–34°, which offers enhanced angular resolution compared with other reported beam-sweeping work. Furthermore, the radiation pattern is continuously steerable.